Synthesis of (E)-vinyl Isobutyronitriles via Fe(III)-catalyzed Decarboxylative Cross-coupling of Cinnamic Acids and AIBN under Additive-free Conditions - Xu, Xuemei; Luo, Zaigang; Fang, Yuyu; Liu, Peng (Letters in Organic Chemistry, 2019)
A facile, efficient, additive-free and eco-friendly protocol for the synthesis of (E)-vinyl isobutyronitriles via Fe(III)-catalyzed decarboxylative cross-coupling of cinnamic acids and AIBN (azodiisobutyronitrile) has been developed. The presented methodology offers several advantages such as easy accessibility and stability of substrates, inexpensive catalyst and simple post-treatment procedure.
Keywords: Decarboxylative cross-coupling